XPS investigation on the reactivity of surface imine groups with TFAA. Issue 4 (25th January 2019) - Kehrer, Matthias; Duchoslav, Jiri; Hinterreiter, Andreas; Cobet, Munise; Mehic, Alen; Stehrer, Thomas; Stifter, David
Abstract : The chemical reaction of imine groups with vapors of trifluoroacetic anhydride (TFAA) was investigated in detail with X‐ray photoelectron spectroscopy (XPS) for the potential application in chemical derivatization (CD) studies of plasma treated surfaces. Imine groups were at first prepared by converting surface amine groups of a polymer precursor using a common vapor phase derivatization reaction with fluorine tagged aldehydes and ketones. The originally low yield for the imine forming reaction of approx. 50%, performed under standard conditions was dramatically enhanced up to 100% by an own developed procedure using a catalyst. This step allowed to obtain a consistent quantification and interpretation of the complex surface reaction products from different types of imine groups derivatized by TFAA. Abstract : A significantly improved chemical derivatization for labeling amine groups with trifluorbenzaldehyde using a catalyzed reaction is presented. This allowed for the first time a consistent quantification and interpretation of the complex surface reaction products from imine groups with trifluoroacetic anhydride.